ANALYSIS OF STUDENTS' CRITICAL THINKING SKILLS IN HISTORY LEARNING: DIAGNOSTIC APPROACH AT SMA NEGERI 2 MEDAN - Anzalimuddin Anzalimuddin; Muhammad Adika Nugraha; Sitti Aisyah (Puteri Hijau : Jurnal Pendidikan Sejarah, 2024)
This research aims to analyze students' critical thinking skills in learning history using a diagnostic approach at SMA Negeri 2 Medan. The research method used is a qualitative descriptive method. The sample for this research was class XI students at SMA Negeri 2 Medan, consisting of 30 students. The instruments used are written tests and observations. The research results show that students' critical thinking skills in history learning tend to be low. Factors that influence students' critical thinking skills include a lack of mastery of historical concepts, a lack of practice in analyzing and evaluating historical information, and a lack of motivation in learning history. Therefore, it is recommended that teachers use a diagnostic approach to help improve students' critical thinking skills in history learning by identifying students' difficulties and weaknesses and providing guidance and learning that suits students' individual needs.